Age-related declines in anaerobic muscular performance: weightlifting and powerlifting - Anton, M. M.; Spirduso, W. W.; Tanaka, H. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: One approach to studying the effects of aging on physiological functional capacity (PFC) in humans is to analyze the peak physical performance of trained athletes with increasing age. The primary aim of the present study was to determine weightlifting and powerlifting performance with increasing age in both men and women. METHODS: We performed a retrospective analysis of top age-group weightlifting and powerlifting records compiled from the U.S. Weightlifting and U.S. Powerlifting Organizations. RESULTS: Regression analyses showed that in both men and women weightlifting and powerlifting performance declined curvilinearly and linearly, respectively. The rate and the overall magnitude of declines in performance with age were markedly greater (P < 0.05) in weightlifting than in powerlifting. The rates of age-related decline in muscular power were not different between upper body (bench press) and lower body (squat). Similarly, the age-related declines were not different between snatch and clean and jerk in weightlifting events. The magnitude of the declines with age was greater (P < 0.05) in women than in men in weightlifting; no such sex-related differences were observed in powerlifting performance. CONCLUSIONS: The findings in this cross-sectional study indicate that 1) peak anaerobic muscular power, as assessed by peak lifting performance, decreases progressively even from earlier ages than previously thought; 2) the overall magnitude of decline in peak muscular power appears to be greater in tasks requiring more complex and powerful movements; 3) the age-related rates of decline are greater in women than in men only in the events that require more complex and explosive power; and 4) upper- and lower-body muscular power demonstrate similar rate of decline with age.